2022
DOI: 10.1111/conl.12905
|View full text |Cite
|
Sign up to set email alerts
|

Beyond inappropriate fire regimes: A synthesis of fire‐driven declines of threatened mammals in Australia

Abstract: Fire can promote biodiversity, but changing patterns of fire threaten species worldwide. While scientific literature often describes ‘‘inappropriate fire regimes’’ as a significant threat to biodiversity, less attention has been paid to the characteristics that make a fire regime inappropriate. We go beyond this generic description and synthesize how inappropriate fire regimes contribute to declines of animal populations using threatened mammals as a case study. We developed a demographic framework for classif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…Altered fire regimes pose a major risk to ecosystems (Flores & Holmgren, 2021;Syphard et al, 2022), biodiversity (Keeley & Pausas, 2019;Kelly et al, 2020), and human life and property (Bushfire Royal Commission, 2020;Gibbons et al, 2012;Moritz et al, 2014). Understanding how they might be changing is critical to making informed decisions about both fire management and ecosystem management (Levine et al, 2022;Santos et al, 2022). Our empirical analyses revealed that fire frequency in Victoria was heterogeneous both in time and in space as indicated by evidence of: (1) a change in the frequency of wildfires over the past 40 years (between 1981 and 2020), with a marked increase in the past 20 years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) relative to the 20 years prior (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000); (2) changes in fire frequency not being spatially uniform, with increases more pronounced i...…”
Section: Discussionmentioning
confidence: 99%
“…Altered fire regimes pose a major risk to ecosystems (Flores & Holmgren, 2021;Syphard et al, 2022), biodiversity (Keeley & Pausas, 2019;Kelly et al, 2020), and human life and property (Bushfire Royal Commission, 2020;Gibbons et al, 2012;Moritz et al, 2014). Understanding how they might be changing is critical to making informed decisions about both fire management and ecosystem management (Levine et al, 2022;Santos et al, 2022). Our empirical analyses revealed that fire frequency in Victoria was heterogeneous both in time and in space as indicated by evidence of: (1) a change in the frequency of wildfires over the past 40 years (between 1981 and 2020), with a marked increase in the past 20 years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) relative to the 20 years prior (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000); (2) changes in fire frequency not being spatially uniform, with increases more pronounced i...…”
Section: Discussionmentioning
confidence: 99%
“…Byram's fire intensity is often used as a metric for decision‐making in fire management, as it ostensibly represents the heat output of the fire (Alexander, 1982). As per the conservation advice for ngwayir, fire risk to fauna is expected to be less when fires are of low intensity (Santos et al, 2022). As shown here, however, Byram's intensity was unrelated to mortality rates, with the slower spread of ‘low intensity’ fires actually related to torching events (Figure 3a–d).…”
Section: Discussionmentioning
confidence: 99%
“…This included 55 threatened species (Wintle et al, 2020). Such changing fire regimes – in particular the increase in intense, large and frequent fires – directly threaten 88% of Australia's threatened land mammals (Santos et al, 2022). In response to these realities, changes to fire regimes in Australia have been recognized nationally as a Key Threatening Process (KTP) (DAWE, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations